Psychological Reactance Theory and Tax Evasion Intentions - Falsetta, Diana (Journal of business ethics, 2026)
This study experimentally examines how tax administration service inefficiencies in the form of tax return processing delays from paper-filed tax returns indirectly affect taxpayer tax evasion intentions through taxpayers’ psychological reactance to the delay. We further consider whether this indirect effect is different when the taxpayer willingly chooses to paper file their tax return versus when the taxpayer is forced to do so. Consistent with Psychological Reactance Theory (PRT), we find that when taxpayers receive delayed refunds, they experience psychological reactance (e.g., anger and frustration with the tax administration) that increases their tax evasion intentions. Further, we find that the effect of a delayed refund on tax evasion intentions via psychological reactance is stronger for taxpayers who choose to paper file than for those who are forced to do so. Our theory and findings inform academics, policymakers, and practitioners about the importance of tax administration services and potential negative taxpayer responses, which could lead to unethical behavior, resulting in increased tax evasion and lost government revenues. Further, our findings provide new insights about PRT when decision-makers face multiple threats versus a single threat to freedom.